The Role of Literal Features During Processing of Novel Verbal Metaphors - Ronderos, Camilo R.; Guerra, Ernesto; Knoeferle, Pia (Frontiers in Psychology, 2021)
When a word is used metaphorically (for example 'walrus' in the sentence "The president is a walrus"), some features of that word's meaning ("very fat", "slow-moving") are carried across to the metaphoric interpretation while other features ("has large tusks", "lives near the north pole") are not. What happens to these features that relate only to the literal meaning during processing of novel metaphors? In 4 experiments, the present study examined the role of the feature of physical containment during processing of verbs of physical containment. That feature is used metaphorically to signify difficulty, such as ‘fenced in’ in the sentence ‘the journalist’s opinion was fenced in after the change in regime’. Results of a lexical decision task showed that video clips displaying a ball being trapped by a box facilitated comprehension of verbs of physical containment when the words were presented in isolation. However, when the verbs were embedded in sentences that rendered their interpretation metaphorical, no such facilitation was found, as evidenced by two eye-tracking reading studies. We interpret this as suggesting that features that are critical for understanding the encoded meaning of verbs but are not part of the metaphoric interpretation are ignored during the construction of metaphorical meaning. Results and limitations of the paradigm are discussed in relation to previous findings in the literature on metaphor comprehension as well as in the literature on the interaction between language comprehension and the visual world.